Diverse Ring‐seco Limonoids from Munronia unifoliolata and Their Biological Activities. Issue 1 (25th November 2021) - Sun, Yunpeng; Li, Qiurong; Cui, Letian; Tang, Pengfei; Li, Yongyi; Kong, Lingyi; Luo, Jun
Comprehensive Summary: Twenty‐two new limonoids, mufolinoids A—V (1—22), including six rings A, B‐ seco limonoids (1—6), twelve ring A‐ seco limonoids (7—18), four ring‐intact limonoids (19—22), together with thirteen known compounds (23—35) were isolated from Munronia unifoliolata . Their structures including absolute configurations were elucidated by combination of NMR, HR‐MS, single‐crystal X‐ray diffraction and calculations of ECD and NMR technologies. Compounds 24, 25, 33, 34 could be significantly reversed the multidrug resistance of MCF‐7/doxorubicin (DOX) cells, and the reversal fold (RF) was much higher than that of positive drug Verapamil. Compounds 24, 28, and 29 exhibited significant anti‐inflammatory activity with the IC50 values in the range of 17.7—39.4 μmol/L. Furthermore, compound 29 could markedly inhibit the release of IL‐1 β by inhibiting the initiation and assembly of NLRP3 inflammasome, which demonstrates the great potential of limonoids as an anti‐inflammatory agent. Abstract : Twenty‐two new limonoids, mufolinoids A−V (1−22), together with thirteen known compounds (23−35) were isolated from Munronia unifoliolata . Compound 29 play anti‐inflammatory effects by inhibiting the initiation and assembly of NLRP3 inflammasome, improving mitochondrial damage, exerting antioxidant effects and inhibiting the release of IL‐6.